Kill Shakespeare – This Bard contains graphic language! (Altre Modernità, 2017)
Today, adapting Shakespearean plays into comic books or graphic novels appears to be a well-established literary practice in contemporary storytelling. One of the most interesting examples is ÒKill ShakespeareÓ, a graphic novel written by Anthony Del Col and Conor McCreery and illustrated by Andy Belanger. In ÒKill ShakespeareÓ, the authors abandon the idea of adapting a single play to create a Shakespearian mashup in which Hamlet and Juliet fight such villains as Richard III and Lady Macbeth who try to kill a wizard named William Shakespeare.This is the premise for a compelling narration that intertwines various elements of the Shakespearean tradition and attempts to convey an idea of Elizabethan language to contemporary readers. While the characters are familiar, the quest is wholly new and triggers a series of transformations in the narrative, turning upside down the well-established images of Hamlet, Juliet and Othello. Beside the intriguing depictions of the female characters, especially Lady Macbeth,whose image poses questions about the representation of women in comic books, one of the most fertile narrative elements in Kill Shakespeare is the actual presence of William Shakespeare as a character. In conclusion, Del Col and McCreery prove they know their Shakespeare, surprising readers with a fresh approach which, hopefully, will enlarge the Shakespearean audience.
Keywords: Shakespeare; comics; graphic novel; adaptation